Determining the presence of a long-term/short-term dilemma for SMEs when adopting strategic orientation to improve performance. (March 2020) - Didonet, Simone Regina; Fearne, Andrew; Simmons, Geoff
This study seeks to discuss a potential 'long-term/short-term dilemma' for small and medium-sized enterprises (SMEs), which could cause tension when adopting two strategic orientations assumed to be complementary – market orientation (MO) and sales orientation (SO). Specifically, the objective of this study is to examine the role of MO and SO as mediators of the relationship between business approach and SME performance. An empirical study of 122 SMEs in the UK grocery sector is conducted. The results reveal that an apparent conflict or tension between market and SO seems to exist in practice. SMEs emphasise both strategic orientations as a way of framing their business approach. However, this emphasis does not hold when considering SME performance. The impact of business approach on performance only occurs through MO. There is no observable significance in the mediation of SO on this relationship. Theoretical and managerial implications for SME management literature and practice are developed.